1979
DOI: 10.1002/bip.1979.360180503
|View full text |Cite
|
Sign up to set email alerts
|

Thermal denaturation of chromatin and lysine copolymer–DNA complexes. Effects of ethylene glycol

Abstract: SynopsisChromatin was thermally denatured in the presence and absence of 1 M ethylene glycol using a technique whereby both the hyperchromism and ellipticity are monitored simultaneously. Model complexes containing PO~Y(L-LYS) or PO~Y(L-LYS, L-Ala, Gly) and DNA were similarly melted in order to assist in interpreting the chromatin results. In both cases a general pattern emerged whereby ethylene glycol perturbed the resultant melting profile, showing increased hyperchromicity, ellipticity, and premelt slope. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Briefly, under current EXPAR conditions, 1.8 M ethylene glycol, 0.8 M propylene glycol, 1 M betaine, 5% DMSO, 0.4 M trehalose and 40 mM TMAC lowered the Tm between target and template by at least 2 °C. Each of those small molecules decreased Tm to different degrees, consistent with the literature152232333435. In contrast, 1 mg/mL BSA and 10 μg/mL SSB proteins had minimal effect on Tm (1 °C or less).…”
Section: Resultssupporting
confidence: 85%
“…Briefly, under current EXPAR conditions, 1.8 M ethylene glycol, 0.8 M propylene glycol, 1 M betaine, 5% DMSO, 0.4 M trehalose and 40 mM TMAC lowered the Tm between target and template by at least 2 °C. Each of those small molecules decreased Tm to different degrees, consistent with the literature152232333435. In contrast, 1 mg/mL BSA and 10 μg/mL SSB proteins had minimal effect on Tm (1 °C or less).…”
Section: Resultssupporting
confidence: 85%
“…Both transitions were irreversible. Schwartz & Pasman (1979) examined the effect of low ethylene glycol levels [1 = 6.2% (w/w)] on the thermal stability of chromatin and lysine copolymer-DNA complexes. They found that ethylene glycol destabilized the high-temperature melting region of the histone-DNA complexes within chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been shown that betaine and ethylene glycol have different affinities to ssDNA and dsDNA (12). It has also been demonstrated that ethylene glycol destabilizes the high melting region of polypeptide-bound DNA and reduces the extent of higher-ordered structure in model complexes and chromatin (13). It appears that ethylene glycol and 1,2-propanediol are able to modulate the annealing process of GC-rich templates, and the ways in which they interact with DNA are different from betaine.…”
mentioning
confidence: 99%